2021
DOI: 10.1037/cep0000241
|View full text |Cite
|
Sign up to set email alerts
|

Sarcasm detection in native English and English as a second language speakers.

Abstract: Sarcastic speech is ubiquitous in most languages, though understanding sarcasm is highly dependent upon cultural and social contextual factors (Campbell & Katz, Discourse Processes, 2012, 49, 459). It is therefore surprising that little research has examined the ability of nonnative speakers to understand the sarcastic cues of a second language. In the current study, native English speakers and English as a second language (ESL) speakers were tested in each of four different conditions. Three of the conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Students with attention deficit/hyperactivity disorder may also benefit greatly from modifications to sensory stimuli, opportunities for movement, and clear expectations for group work or presentations. Likewise, avoiding sarcasm or figures of speech can benefit not only autistic students, but also may benefit some students who are in the process of learning English as their nonprimary language (Techentin et al, 2021). Finally, ensuring that a robust accommodations framework is in place can benefit the many students who will at some point need temporary accommodations due to various circumstances (e.g., loss in the family, illness, etc.…”
Section: Addressing Potential Concerns and Next Stepsmentioning
confidence: 99%
“…Students with attention deficit/hyperactivity disorder may also benefit greatly from modifications to sensory stimuli, opportunities for movement, and clear expectations for group work or presentations. Likewise, avoiding sarcasm or figures of speech can benefit not only autistic students, but also may benefit some students who are in the process of learning English as their nonprimary language (Techentin et al, 2021). Finally, ensuring that a robust accommodations framework is in place can benefit the many students who will at some point need temporary accommodations due to various circumstances (e.g., loss in the family, illness, etc.…”
Section: Addressing Potential Concerns and Next Stepsmentioning
confidence: 99%
“…Research has also been extended beyond the English language. Techentin et al [43] studied the sarcasm of native and non-native English speakers. They identified that certain experience features play a role in the ability of non-native speakers to identify and use sarcastic cues.…”
Section: Related Workmentioning
confidence: 99%
“…Various languages across the globe have witnessed the development of machine learning models tailored for detecting sarcasm, enriching communication analysis across diverse linguistic landscapes. In English, researchers have pioneered advanced models utilizing sophisticated natural language processing techniques to discern sarcastic utterances amidst regular text [4]. Similarly, in Hindi, the intricate interplay of the language's extensive vocabulary and nuanced expressions has prompted investigations into sarcasm detection models, facilitating more accurate sentiment analysis in social media and textual communication [5].…”
Section: Introductionmentioning
confidence: 99%